Electronic vs. Geometric effects of Al2O3-supported Ru species on the adsorption of H2 and substrate for aromatic LOHC hydrogenation - Kim, Tae Wan; Chun, Hee Joon; Jo, Yeongin; Kim, Dongun; Ko, Hyerim; Kim, Soo Hyun; Kim, Seok Ki; Suh, Young Woong (Journal of Catalysis, 2023)
The intrinsic rate of aromatic hydrogenation is tuned by electronic and geometric characters of active metals. Herein, Ru/Al2O3 catalysts were prepared by varying the Ru loading from 0.25 to 12 wt% and tested in the hydrogenation of toluene and (di)benzyltoluene well-known as hydrogen carriers. At lower Ru loadings (<5 wt%), Ru nanoclusters smaller than 0.82 nm with strong Ru–Al2O3 interaction were formed, enriching electron-deficient Ru atoms for activity-unfavorable H2 adsorption. In contrast, Ru nanoparticles larger than 0.82 nm with weak Ru–Al2O3 interaction were produced at higher Ru loadings (>5 wt%), making larger Ru0 slabs for activity-unfavorable substrate adsorption. The kinetic barrier was higher for strong Ru–Al2O3 interaction or for the Ru species similar to close-packed Ru. The identified electronic and geometric properties of Ru species guaranteed the structure-sensitivity of Ru/Al2O3-catalyzed aromatic hydrogenation, recommending small-sized Ru species close to zero valence for accelerated aromatic hydrogenation.
Keywords: Aromatic hydrogenation; Geometric effects; Geometric properties; Intrinsic rates; Metal-support interactions; Rate of aromatics; Ru catalysts; Ru species; Structure sensitivity; Supported ru catalyst; Aromatic hydrogenation; Electronic properties; Geometric properties; Metal–support interaction; Structure-sensitivity; Supported Ru catalysts